Factors affecting knowledge sharing on innovation in the higher education institutions (HEIs) - Mohammad , Mozammel Haque; Ahlan, Abdul Rahman; Mohamed Razi, Mohamed Jalaldeen (Asian Research Publishing Network (ARPN), 2015)
It is believed that Information and Communication Technology (ICT) can enhance Knowledge Sharing (KS) with the integration of individual and organizational factors. As a relatively new field of research, studies on KS based on Information Systems (IS) in developed countries is also on the increase. Unfortunately, KS research in the Higher Education Institutions (HEIs) in developing countries is mostly found to be given trivial considerations. It is even rare to find conceptual research model for KS in HEIs in developing countries that integrate individual, organizational and technological antecedent factors together. Therefore, the objectives of this paper are twofold: (i) to explore the best conceptual KS research frameworks based on existing research models in HEIs; and also (ii) to propose a research model that can help explain better the nature of KS in HEIs. The methodology of this study is subjective/argumentative research i.e. idea generation in IS. The proposed research model has been built on the basis of IS theories and from the review of extant KS literature. The study reveals the antecedents and incorporates in the proposed research models which are: perceived self-efficacy for higher education and training, perceived leadership, social network, perceived ICT tools and technology, perceived organizational rewards, perceived organizational climate and perceived organizational trust. The paper explains the antecedents, relevance and theoretical applicability for the integration of the three theories in KS research for HEIs. The finding of this study reveals that the proposed KS research model seems better compare to other existing KS research framework in HEIs in developing countries. The study also reveals that the IS theories integration with ICT technology can explain better for KS research.